Place attachment in informal settlements: the influence of community leaders in Mexico - Rojas Rivera, Concepcion del Carmen (2020)
The research questions explored in this study are: “How is place attachment built and nurtured in informal settlements within impoverished communities in Mexico?”, and “What is the role of community leaders in this context?”. Informal settlement’s development, formalization, relocation or failure rests mainly on the actions of its residents rather than on the governance and policies of authorities. Community leaders are critical figures within the community; however, research on leadership in informal settlements has been rarely studied due to difficulties in accessing communities and communicating with authorities. Additionally, literature about how leadership influences socio-spatial relationships amongst residents is scarce. Thus, this research examines how different community leaders directly or indirectly influence this process. Place attachment studies on informal settlements generally tend to focus on the place-making activities that a community engages in and the feelings of attachment that result (Lombard, 2014). Defining the variables that affect place attachment in informal settlements is crucial to understanding how they function, especially towards development or relocation processes.